ANALISA YURIDIS PERTANGGUNG JAWABAN DIREKSI PADA PENGADAAN BARANG/JASA DI PT. BANK SUMUT (STUDI : PUTUSAN TIPIKOR PENGADILAN NEGERI MEDAN NO. 93/PID.SUS-TPK/2016/PN.MDN. JO. PUTUSAN PENGADILAN TINGGI MEDAN NO. 06/PID.SUS-TPK/2017/PN.MDN.) - Muhammad Iqbal; Sunarmi Sunarmi; Budiman Ginting; Faisal Akbar (USU LAW JOURNAL, 2018)
ABSTRACT The Board of Directors shall be the management of the company representing the company, both inside and outside the court. The legal norms implied in the provision that all corporate liabilities, both represent and management of the company, are on the shoulders of directors. In accordance with Article 97 paragraph (2) of Law no. 40 of 2007 regarding Limited Liability Company, states that: "The management of the company shall be carried out by every member of the Board of Directors in good faith and full of responsibility". If it is associated with the "Business Judgment Rule" doctrine being taught, the responsibility of the board of directors, the principle of "fiduciary duty". In this study will discuss: Implementation of procurement of goods / services within the Government (L / K / D / I), BUMN / D is associated with the source of funds derived from APBN / D; Legal consequences of directors' liability in the Annual General Meeting of Shareholders of the Company which have been declared acquit et decharge by shareholders; and the accountability of the Board of Directors of PT. Bank of North Sumatra in the procurement of rental vehicles and operational vehicles of PT. Bank Sumut Year 2013 in the Corruption Court's Ruling At the Medan District Court. 93 / Pid.Sus-TPK / 2016 / PN.Mdn. Jo. High Court of Medan Decision. 6 / Pid.Sus-TPK / 2017 / PT.Mdn.   Keywords          :     Accountability of the Board of Directors; PT. Bank Sumut; Procurement of Goods / Services.